2015
DOI: 10.1373/clinchem.2015.242743
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Early Rule-Out Strategies for Acute Myocardial Infarction: Utility of 1-Hour Copeptin

Abstract: BACKGROUND: Combined testing of high-sensitivity cardiac troponin T (hs-cTnT) and copeptin at presentation provides a very high-although still imperfect-negative predictive value (NPV) for the early rule-out of acute myocardial infarction (AMI). We hypothesized that a second copeptin measurement at 1 h might further increase the NPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…25,26 Fourth, serial measurements of copeptin at 1h or 2h are not recommended in routine clinical use as serial measurements provide very little additional information, and are inferior to serial measurements of cTn. 21,32 Fifth, we have to acknowledge that our current understanding of the exact pathophysiology of copeptin is still rather incomplete; for example, case reports indicate elevated blood concentrations also in patients presenting with vasovagal syncope to the ED (Case 3 in Supplementary Material online). It is unknown whether outcome differs in syncope patients with high copeptin blood concentrations as compared with those with normal levels.…”
Section: How To Use Copeptinmentioning
confidence: 99%
“…25,26 Fourth, serial measurements of copeptin at 1h or 2h are not recommended in routine clinical use as serial measurements provide very little additional information, and are inferior to serial measurements of cTn. 21,32 Fifth, we have to acknowledge that our current understanding of the exact pathophysiology of copeptin is still rather incomplete; for example, case reports indicate elevated blood concentrations also in patients presenting with vasovagal syncope to the ED (Case 3 in Supplementary Material online). It is unknown whether outcome differs in syncope patients with high copeptin blood concentrations as compared with those with normal levels.…”
Section: How To Use Copeptinmentioning
confidence: 99%
“…Therefore, a strategy using baseline and 1-hour hsTnT testing and the 99th percentile upper reference limit missed only 3 patients with acute MI (1.1% of all MIs). 12 In that study, among the 25% of patients with an hsTnT value below the limit of detection (<5 ng/L) at presentation, the NPV for MI was already 99.7%, suggesting that serial testing may be unnecessary in such patients. Similarly, Shah and colleagues 13 reported that, among 4870 patients presenting with chest symptoms, the optimal threshold for ruling out MI with a single hsTnI concentration determined at presentation was less than 5 ng/L (approximately 50% of the population) with an NPV of 99.6%.…”
Section: Leveraging the Sensitivity In Hstn Assaysmentioning
confidence: 79%
“…The cited literature (Boeddinghaus et al, 2017, Hillinger et al, 2015, Mueller et al, 2018, Mueller-Hennessen et al, 2019, Stallone et al, 2016, O'Donoghue et al, 2006 is not a level B evidence for any recommendation against the DMS or the use of fatty acid binding protein (FABP). Therefore, the recommendation of the guidelines base on a consensus of the involved experts (level C) and is not explained or supported by the cited literature.…”
Section: Editorialmentioning
confidence: 99%